PEMBERDAYAAN KELOMPOK USAHA KOPI BOY MELALUI INOVASI PRODUK DAN DIGITAL MARKETING DI JEPARA - Saputro, Heru; Prihatmoko, Dias; Mudiarti, Luky; Aulia, Elza Nur; Choirunisa, Vika (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Community Partnership Program (PKM) was implemented to empower the youth-managed business group “Kopi Boy” in Demaan Village, Jepara Regency. The partner faced key challenges, including limited product innovation, inefficient manual production processes, and conventional marketing practices without digital support. The objective of this program is to enhance production capacity, strengthen product innovation, and improve the partners’ digital marketing skills to compete in the modern beverage market. The implementation methods include socialization, training on product innovation and financial management, the application of production technology (electric grinder and coffee press), digital marketing assistance through social media, and evaluation of program outcomes. The activities were conducted from February to May 2025 at the Kopi Boy coffee shop, involving 10 business group members, 3 lecturers, and 2 students from Universitas Islam Nahdlatul Ulama Jepara. The results show a significant improvement in various business aspects. Production capacity increased from 300 to 800 cups per day, the number of coffee variants expanded from one to ten, and monthly turnover rose by 100%. In terms of marketing, the partner successfully developed a new brand identity and optimized social media platforms, as reflected in the growing number of followers on TikTok, Instagram, and Facebook. In conclusion, this PKM program successfully enhanced the business independence, product creativity, and managerial capabilities of KUB Kopi Boy. In addition to providing direct economic benefits, the program also strengthened the role of youth in the digital-based creative economy and has the potential to be replicated for other youth business groups in Jepara Regency.Program Kemitraan Masyarakat (PKM) ini dilaksanakan untuk memberdayakan Kelompok Usaha Bersama (KUB) “Kopi Boy” yang dikelola oleh pemuda di Desa Demaan, Kabupaten Jepara. Mitra menghadapi permasalahan utama berupa keterbatasan inovasi produk, proses produksi manual yang tidak efisien, dan pemasaran yang masih konvensional tanpa dukungan teknologi digital. Tujuan kegiatan ini adalah meningkatkan kapasitas produksi, kemampuan inovasi produk, dan keterampilan digital marketing mitra agar mampu bersaing di pasar minuman kekinian. Metode pelaksanaan meliputi sosialisasi, pelatihan inovasi produk dan manajemen keuangan, penerapan teknologi produksi (grinder listrik dan coffee press), pendampingan pemasaran digital melalui media sosial, serta evaluasi hasil kegiatan. Kegiatan berlangsung selama Februari–Mei 2025 di kedai Kopi Boy dengan melibatkan 10 anggota mitra, 3 dosen, dan 2 mahasiswa dari Universitas Islam Nahdlatul Ulama Jepara. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada berbagai aspek usaha. Kapasitas produksi meningkat dari 300 menjadi 800 cup per hari, jumlah varian kopi bertambah dari satu menjadi sepuluh, serta omzet bulanan naik sebesar 100%. Dari sisi pemasaran, mitra berhasil membangun identitas merek (branding) baru dan mengoptimalkan media sosial, yang terbukti dari peningkatan jumlah pengikut di TikTok, Instagram, dan Facebook. Kesimpulannya, kegiatan PKM ini berhasil meningkatkan kemandirian usaha, kreativitas produk, dan kemampuan manajerial KUB Kopi Boy. Selain memberikan dampak ekonomi langsung bagi mitra, program ini juga memperkuat peran pemuda dalam ekonomi kreatif berbasis digital dan berpotensi untuk direplikasi pada kelompok usaha muda lainnya di Kabupaten Jepara.